Le meilleur promoteur dans quel sens ? A closer look at French sluicing (with extra elements) - Temmerman, Tanja (Nordlyd, 2026)
This paper addresses French sluicing, focusing on constructions in which a wh-remnant co-occurs with a non-wh-element, collectively referred to as Sweeping (Sluicing With Extra Elements Persist-ing, Temmerman 2019). Building on prior work, it introduces a previously undescribed subtype: IWW-sluicing, involving the wh-phrase dans quel sens (‘in what way’), and draws parallels with comment-sluicing (with the wh-phrase comment ‘how’). I propose that these two types of Sweeping function as clarification requests targeting the interpretation of a repeated expression, namely the extra non-wh-remnant, which displays properties of a mixed-quoted expression. It is further argued that the explicit clarification request underlying these sluices takes on the form of a short cleft. The paper also brings a third type of Sweeping, SpaCing (Sluicing with a Ça ‘that’), into the empirical picture, showing that only minimal wh-phrases such as comment can combine with ça, whereas complex wh-phrases like dans quel sens cannot. The findings challenge in situ deletion accounts and support a unified, ellipsis-based analysis of different types of French sluicing, including cases in which the sluice is accompanied by extra elements.
Keywords: French – Ellipsis - Sluicing – Sweeping – Spading